Selected non-communicable diseases and risk conditions among fishermen in Divisional Secretariat Division of Kalpitiya - S.R.A.P. Harshani; Chrishantha Abeysena (College of Community Physicians of Sri Lanka, 2017)
Introduction Fishermen are special group of people who are more vulnerable to non-communicable diseases due to occupation specific conditions. Objective To determine the prevalence of accidental injuries, hypertension, malnutrition, smoking and alcohol consumption among fishermen in Divisional Secretariat Division of Kalpitiya. Methodology This was a descriptive cross-sectional study, conducted during the period of August to October 2011. The sample consisted of 465 fishermen with ≥6 months experience in fishing and selected by applying the cluster sampling technique. The study instruments were the interviewer-administered questionnaire and the record sheet. Prevalence of the above conditions and diseases with 95% confidence intervals (CI) were calculated. Results The prevalence of accidental injuries was 19.6%(95%CI:16%-23.2%). The prevalence of hypertension was 24.3%(95% CI:20.4%-28.2%) and it was significantly higher among those who have >10 years of service experience in the fishing sector (p<0.01) and history of smoking >10 years duration (p<0.001). The prevalence of underweight, overweight and obesity were 6.2%(95%CI:4%-8.4%), 20.6%(95%CI:16.9%-24.3%) and 2.6%(95%CI:1.2%-4%) respectively. The prevalence of current smokers and current alcohol consumers were 54.6%(95% CI: 50.2%-59%) and 60.2%(95% CI: 55.8%-64.6%) respectively. Conclusion The prevalence of hypertension, smoking and alcohol consumption were higher and obesity was lower among fishermen than general population. Improve the knowledge on prevention and screening are recommended.